Pengembangan Mata Kuliah Praktek Kejuruan Bagi Mahasiswa Jptm Fptk Upi Yang Relevan Dengan Kebutuhan Sebagai Calon Guru Smk Bidang Teknik Mesin - Wardaya, Wardaya; Purnawan, Purnawan; Sasmita, Asep H. (INVOTEC, 2010)
Between development aim a curriculum relevance enhanced, that is existence the relevance between matter that developed with the user need. This watchfulness aim was to produce subject matter development plan of vocational practice at JPTM FPTK UPI that can increase relevance with vocational practice teachercompetence need at SMK in mechanical engineering field. Watchfulness uses method descriptive. Data is gathered to pass documentation study and observation. Data source shaped from SMK curriculum document in mechanical engineering field and curriculum of JPTM FPTK UPI on Design and Production skill area group. Watchfulness result shows; (1) found 19 practice competence kinds productive at SMK in mechanical engineering. Competences can be grouped in 4 groups, that is drawing, practice base, machinery conventional manual, and machinery conventional CNC. (2) Produced development and pattern plan of vocational practice subject matter that is composed based on sequence matter contents. Mapping of vocational practice subject matter that designed: picture competence presents in semester 1,2 and 5, practice competences base present in semester 2,4 and 5, competences machinery conventional manual present in semester 3 and 4, competences machinery conventional CNC present in semester 6 and 7.